К.РАХМАНОВТЫҢ «АҚЫБЕТ» РОМАНЫНДА ФРАЗЕОЛОГИЗМЛЕРДИҢ ҚОЛЛАНЫЛЫЎ ӨЗГЕШЕЛИКЛЕРИ - Досжанова, Г.Д. (SCIENCE and SOCIETY, 2017)
The article is devoted to the study of phraseologisms used in the novel “Akibet” by K.Rakhmanov. The author of the article analyses peculiarities of using pharaseological synonyms and variants.
Keywords: phraseologism; pharaseological synonym; synonym; pharaseological variant; semantic; vocabulary; lexical variant; grammatical variant